Perbedaan Daya Anthelmintik antara Ekstrak Daun Pepaya (Carica papaya, Linn.), Daun Pare (Momordica charantia, Linn.), dan Kombinasi Keduanya terhadap Cacing Ascaris suum, Goeze in Vitro - Nurul Rahmawati Swadini; Sri Haryati; Bambang Sukilarso Sakiman (Nexus Biomedika, 2013)
Backgrounds: Ascariasis is an infection disease caused by Ascaris lumbricoides, Linn. Drugs therapy for ascariasis has various side effects causing unpleasant sensation to the patient such as nausea, vomiting, diarrhea, and constipation. Infusion of papaya leaves and bitter gourd leaves contains saponin and tannin known having anthelmintic activity. This experiment aimed to find out the difference of anthelmintic capacity among papaya leaves extract, bitter gourd leaves extract and their combination to Ascaris suum, Goeze, in vitro. Methods: This experiment was quasi experiment with post test only controlled group design. Subject for this experiment was Ascaris suum, Goeze. The subject was arranged into five groups, those were negative control group (NaCl 0.9%), positive control group (Pirantel pamoat 5 mg/ml), papaya leaves extract group, bitter leaves extract group and the combination of both papaya and bitter gourd leaves extract group. The extract concentrations for the treatment were 40%, 50%, 60%, 70%, and 80% w/v. Subjects were dipped into extract for maximum monitoring time. Death time of all worms in each group was examined. Data were analyzed with linear regression and probit analysis (? = 0.05). Results: Regression analysis showed that there was a significant relation between death time and concentration of papaya leaves extract, bitter gourd leaves extract, and combination of both with significance value p = 0,000 (p < 0.05). Probit analysis showed that combination of papaya leaves and bitter gourd leaves extract was more effective than Pyrantel pamoate. Conclusions: There were differences of anthelmintic capacity among papaya leaves extract, bitter gourd leaves extract and their combination. The combination of both papaya leaves extract and bitter gourd leaves extract as anthelmintic was more effective than they were alone and also more effective than Pyrantel pamoate. Keywords: Anthelmintic capacity, papaya leaves extract, bitter gourd leaves extract, combination